Alcohol Acyltransferase Is Involved in the Biosynthesis of C6 Esters in Apricot (Prunus armeniaca L.) Fruit - Zhou, Wanhai; Kong, Wenbin; Yang, Can; Feng, Ruizhang; Xi, Wanpeng (Frontiers in Plant Science, 2021)
Short-chain esters derived from fatty acid contribute to the characteristic flavor of apricot fruit, and the biosynthesis of these compounds in fruit is catalyzed by alcohol acyltransferase (AAT). In this work, we investigated the AAT gene family via genome-wide scanning, and three AAT loci were identified in different linkage groups (LGs), with PaAAT1 (PARG22907m01) in LG7, PaAAT2 (PARG15279m01) in LG4, and PaAAT3 (PARG22697m01) in LG6. Phylogenetic analysis showed that PaAAT1 belongs to clade 3, while PaAAT2 and PaAAT3 belong to clade 1 and clade 2, respectively. In contrast, the three AAT genes present different expression patterns. Only PaAAT1 exhibited distinct patterns of fruit-specific expression, and the expression of PaAAT1 sharply increased during fruit ripening, which is consistent with the abundance of C4-C6 esters such as (E)-2-hexenyl acetate and (Z)-3-hexenyl acetate. The transient overexpression of PaAAT1 in Katy (KT) apricot fruit resulted in a remarkable decrease in hexenol, (E)-2-hexenol, and (Z)-3-hexenol levels while significantly increasing the corresponding acetate production (p < 0.01). A substrate assay revealed that the PaAAT1 protein enzyme can produce hexenyl acetate, (E)-2-hexenyl acetate, and (Z)-3-hexenyl acetate when C6 alcohols are used as substrates for the reaction. Taken together, these results indicate that PaAAT1 plays a crucial role in the production of C6 esters in apricot fruit during ripening.